2015
DOI: 10.1109/lpt.2015.2439576
|View full text |Cite
|
Sign up to set email alerts
|

Ho:KLu(WO<sub>4</sub>)<sub>2</sub> Microchip Laser Q-Switched by a PbS Quantum-Dot-Doped Glass

Abstract: We report on passive Q-switching of a Ho:KLu(WO 4 ) 2 (Ho:KLuW) microchip laser in-band-pumped by a Tm:KLuW laser at ~1.96 μm. As a saturable absorber, PbSquantum-dot-doped glass was used which exhibits a saturation intensity of ~3 MW/cm 2 near 2 μm. Maximum average output power of 84 mW was achieved from the Ho laser at 2.061 µm with a slope efficiency of 42% (with respect to the absorbed pump power). The shortest pulse duration was 30 ns. In the continuous-wave mode, the maximum output power of the Ho laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Zhang reported a PQS Tm,Ho:YLF laser with Cr 2+ :ZnS SA, the pulse width was about 1.25 µs, with the pulsed energy of 4 µJ [6]. In the same year, Loiko et al proved the feasibility of using PbS quantum-dot-doped glass as SA in a Ho:KLu(WO 4 ) 2 laser, acquired the maximum average output power of 84 mW and the shortest pulse duration of 30 ns [7]. In 2014, S. Wang et al reported a MoS 2 passively Q-switched Tm:Ho:YGG laser with 410-ns pulses and 206-mW average output power [8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang reported a PQS Tm,Ho:YLF laser with Cr 2+ :ZnS SA, the pulse width was about 1.25 µs, with the pulsed energy of 4 µJ [6]. In the same year, Loiko et al proved the feasibility of using PbS quantum-dot-doped glass as SA in a Ho:KLu(WO 4 ) 2 laser, acquired the maximum average output power of 84 mW and the shortest pulse duration of 30 ns [7]. In 2014, S. Wang et al reported a MoS 2 passively Q-switched Tm:Ho:YGG laser with 410-ns pulses and 206-mW average output power [8].…”
Section: Introductionmentioning
confidence: 99%